2022
DOI: 10.1111/jcmm.17543
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of EBV‐DNA status with the prognosis of lymphoma

Abstract: Epstein–Barr virus (EBV) infection is proved to be associated with clinicopathology of lymphoma. However, little is known about the relationship between EBV‐DNA status after treatment and prognosis. In this study, real‐time polymerase chain reaction (PCR) was used for quantitative detection of EBV‐DNA load in peripheral blood of all 26,527 patients with lymphoma, and the clinical characteristics and prognosis of 202 patients were retrospectively analysed, including 100 patients with positive EBV‐DNA and 102 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Multivariate analysis further demonstrated that DNA4 had an independent effect on the prognosis of PTCL for OS. Consistent with previous studies by Song et al ( 2022 ), Shen et al ( 2022 ), and Qiu et al ( 2022 ), EBV DNA emerged as an effective prognostic marker. It appears that EBV DNA may be superior to EBER, possibly because EBER is a qualitative diagnostic index derived from tissue samples, whereas EBV DNA is a quantitative measurement analyzed from plasma samples.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Multivariate analysis further demonstrated that DNA4 had an independent effect on the prognosis of PTCL for OS. Consistent with previous studies by Song et al ( 2022 ), Shen et al ( 2022 ), and Qiu et al ( 2022 ), EBV DNA emerged as an effective prognostic marker. It appears that EBV DNA may be superior to EBER, possibly because EBER is a qualitative diagnostic index derived from tissue samples, whereas EBV DNA is a quantitative measurement analyzed from plasma samples.…”
Section: Discussionsupporting
confidence: 90%
“…DNA was extracted from plasma samples using the EBV PCR Fluorescence Quantitative Diagnostic Kit. Copy numbers were analyzed using a standard curve, with 500 copies/mL defined as the critical value based on previous studies (Kim et al 2021 ; Shen et al 2022 ; Zeng et al 2022 ; Qiu et al 2022 ). If EBV DNA was less than 500 copies/mL, it was recorded as 0.…”
Section: Methodsmentioning
confidence: 99%